Optical Properties of BaAl2O4 Due to Cerium Doping and Heat Treatment in Different Atmospheres - Montserrat Nevai Coyotl Ojeda; Benito de Celis Alonso; José Eduardo Espinosa Rosales; Epifanio Cruz-Zaragoza; Martín Rodolfo Palomino Merino (Micromachines)
The luminescent properties of cerium-doped barium aluminate (BaAl2O4) samples with varying Ce concentrations (0–1.1 mol%) prepared either in an air or nitrogen-reduced atmosphere are presented. This work provides the first detailed comparison of the material’s structural, luminescent, and chromatic properties at different doping levels and thermal treatments. X-ray diffraction analysis confirmed the hexagonal crystal structure of barium aluminate. Samples treated in an air atmosphere exhibited crystallite sizes of 58.5 nm for undoped samples and 45.7 nm for doped samples. In contrast, those treated under nitrogen showed smaller crystallite sizes, i.e., 39.8 nm for undoped and 42.3 nm for doped samples, respectively. XPS analysis indicated that the nitrogen-reduced atmosphere minimized Ce oxidation, favoring the presence of Ce3+. The bandgap values of the material were 4.0 eV and 5.6 eV for the air and for the nitrogen atmosphere, respectively. Photoluminescence spectra showed maxima at 357 nm (air) and 386 nm (nitrogen), attributed to 4f-5d transitions of Ce. The samples under air atmosphere showed longer lifetimes values (0.94 ns) compared to those in a nitrogen atmosphere (0.40 ns). These results suggest that thermal treatment in an air atmosphere promoted better structural order and higher photoluminescence efficiency, while treatment in a nitrogen-reduced atmosphere increased defect formation, shortening the lifetime. Chromaticity coordinate analysis showed that the cerium ion dopant influenced the blueish emission color in both samples.